The long‐term effects of prolonged intensive care stay postcardiac surgery. Issue 11 (25th August 2020) - Mackie‐Savage, Ursula F.; Lathlean, Judith
Abstract: Objectives: Short‐term outcomes for those with a prolonged length of stay (LOS) in intensive care (ITU) following cardiac surgery are poor, with higher rates of in‐hospital mortality and morbidity. Consequently, discharge from hospital has been considered the key measure of success. However, there has been a shift towards long‐term outcomes, functional recovery and quality of life (QoL) as measures of surgical quality. The aim of this review is to compare and critique the findings of multiple studies to determine the long‐term effects of prolonged ITU stay postcardiac surgery. Methods: A computerized literature search of CINAHL, EMBASE and Google Scholar databases, based on keywords "long‐term effects, " "prolonged ITU stay, " "cardiac surgery, " with rigorous CASP critique was undertaken. Results: The search yielded 12 papers meeting the inclusion criteria, with eight retrospective and four prospective studies. Eight of these 12 papers identified inferior long‐term survival or higher mortality rates for those who had prolonged LOS in ITU in comparison to "normal" LOS or a control. The greatest burden of mortality was 6 months to 1 year postdischarge. Three papers found that quality of life was adversely affected or worse for those who had experienced prolonged LOS in ITU. Conclusions: Further research is required to provide better quality evidence into QoL, following prolonged stay in ICU postcardiac surgery. The evidence reviewed suggests that the risk of mortality in this demographic of patients is higher, especially within the first year and, therefore, more frequent medical surveillance of these patients is recommended.